THE EFFECT OF SOYBEAN PRODUCTION AND IMPORTS ON SOYBEAN PRICES IN INDONESIA - Aulia Maharani Br Purba; Reza Juanda; Nabila Ramadina (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to analyze the influence of soybean production and soybean imports on soybean prices in Indonesia. This study uses time series data from 1990-2024 using multiple linear regression methods. The results show that soybean production has a negative and significant effect on soybean prices in Indonesia. Conversely, soybean imports have a positive and significant effect on soybean prices in Indonesia. Simultaneously, soybean production and soybean imports significantly influence soybean prices in Indonesia.